Assessing the Impact of Socioeconomic Factors on Suicide: A Panel Study in ASEAN Countries - Kwang Hui, Hon; Jerome Swee Hui, Kueh; Shirly Siew Ling, Wong (International Journal of Academic Research in Business and Social Sciences, 2024)
This paper examines the impact of socioeconomic factors on ASEAN’s suicide from year 2000 to 2019. Both linear and non-linear connection between age-standardised total suicide rate with per capita GDP, current health spending, unemployment rate, fertility rate, female labour force participation rate and per capita alcohol consumption are examined utilising a panel data obtained from WHO and The World Bank. This study is based on the panel unit root tests, panel cointegration test, panel ARDL estimation and differential calculus approach turning point estimation. The panel unit root tests resulted that all variables are stationary at I(0), I(1) or both levels. The long-run association between variables in ASEAN countries is found in Pedroni cointegration test. The results from panel ARDL presented that all socioeconomic factors are significantly related to age-standardised total suicide rate. Additionally, per capita GDP showed the linkage of U-shaped with age-standardised total suicide rate, with the estimated turning point at about $65,150.00 USD after which higher GDP per capita are linked to a higher age-standardised total suicide rate in ASEAN countries.